Manajemen Sistem Penjaminan Mutu Internal Pendidikan Di SMK Negeri 2 Kebumen - Solikhudin Solikhudin (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This research is based on the importance of an internal education quality assurance system. In this regard, this study aims to determine the management of the internal quality assurance system of education at SMK N 2 Kebumen. This study uses qualitative research that focuses on natural empirical phenomena and is analyzed using scientific logic. The data collection techniques in this study were obtained through observation, interviews, documentation and triangulation. Data analysis was carried out by data reduction, data presentation, and data verification then formulating conclusions on the results of the research conducted. There are four findings in this study, namely: (1) Internal Quality Assurance Planning at SMK N 2 Kebumen is carried out through three stages, namely: (a) setting quality standards, which refer to the 8 National Education Standards, (b) quality mapping, which based on the results of the School Self-Evaluation, and (c) preparation of a quality compliance plan, which is carried out with preparation prior to the preparation of the Medium Term Work Plan and Annual Work Plan; (2) Implementation of quality fulfillment at SMK N 2 Kebumen is carried out by fulfilling 8 National Education Standards. All components of the school have a high commitment in implementing quality compliance; (3) Quality Fulfillment Evaluation at SMK N 2 Kebumen is carried out through School Self-Evaluation. Beginning with compiling evaluation instruments and then forming an evaluation implementation team. The evaluation is carried out by identifying physical evidence of the condition of the school; (4) Quality Fulfillment Follow-up at SMK N 2 Kebumen is carried out by formulating recommendations for improvement. There are two types of actions taken based on the results achieved, namely: (a) Corrective Action and (b) Standardization Action. Follow-up of quality fulfillment at SMK N 2 Kebumen is a continuous cycle (Continuous Process Improvement).